) كمورد بيئي بنائي مستدام Posidonia oceanica تالغا ( (استبيان عن وعي المجتمع والمتخصصين ومدى استعدادهم للتبنيه) (Comprehensive Journal of Science, 2025)
Posidonia oceanica is a species of seagrass endemic to the Mediterranean Sea, forming vast underwater meadows. When its leaves decompose, they are transported to the shore, where they accumulate in large piles that serve to protect coastlines from marine erosion. Its roots and rhizome fragments aggregate into fibrous sea balls known as egagropili, which are shaped and deposited along the beach by wave action. Although these formations are often considered undesirable by tourists, and are commonly treated by local communities as waste to be removed, they may, in fact, represent a valuable plant biomass. This biomass could be harnessed as a renewable substrate for producing bio-absorbent materials in environmental remediation, or as an insulating and reinforcing material for sustainable construction.This paper aims to explore public awareness and acceptance of this natural and bio-based material through a survey, analyzing its results and highlighting the main characteristics and potential applications of Posidonia oceanic in various fields—particularly as an effective and sustainable material. The discussion is supported by a review of recent scientific literature published in the past few years
Keywords: Cellulose; Egagropili; Biomass; Lignin; Marine Waste; Construction Reinforcement; Sustainable